Sir Cecil Spring Rice papers - Spring Rice, Cecil, Sir, 1859-1918.
Letters (1917-1918) of Spring Rice and his wife, Florence Spring Rice, to Eugene Tyler Chamberlain, Charles Moore, and others; two letters (1917) between Charles Moore and Frank C. Munson; typescript of an untitled poem and photocopies of printed versions of Spring Rice's poems, "Katie's Forest Friends" and "Sonnets from the Persian"; typescript of a tribute to Spring Rice (1918) and program from a memorial service for him at Washington Cathedral (1918 February 16); and a wax seal.
In part, negative photocopies and typewritten transcripts.
British ambassador to the United States and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chamberlain, Eugene Tyler, -- 1856-1929 -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence..; Munson, Frank C., -- 1876-1936 -- Correspondence; Spring Rice, Florence -- Correspondence; Washington Cathedral; Diplomatic and consular service, British -- United States; English poetry; Memorials; Authors; Diplomats -- Great Britain